The Influence of Product Quality and Price on the Purchase Decision of Car Spare Parts in Retail Stores - Firmansyah, Yusril; Irsandi; Sakti, Trenggono; Asfarani, Suci (Indonesian Journal Publisher, 2025)
This study aims to examine the influence of product quality and price on purchasing decisions at Obama Motor, an automotive parts retailer in Pringsewu. The research problem focuses on how product quality and price affect consumer purchasing decisions. A quantitative approach was used with a sample of 44 respondents selected randomly. Data were collected through surveys, and multiple regression analysis was applied. The results showed that both product quality (β = 0.344) and price (β = 0.435) significantly affect purchasing decisions. The conclusion of this study is that maintaining high product quality and competitive pricing is essential to improve customer satisfaction and loyalty in the automotive market.